The Characteristics of Adsorption of Di-n-Butyl Phthalate by Surface Sediment from the Three Gorges Reservoir - Yuting Zhang; Min Liu; Li Lin; Liangyuan Zhao; Wei Deng; Cheng Han; Mingli Wu (Toxics, 2024)
Phthalic acid esters (PAEs), recognized as endocrine disruptors, are identified as predominant organic pollutants in the Three Gorges Reservoir (TGR). Di-n-butyl phthalate (DBP), a representative PAE, has been extensively studied for its sources, distribution and ecological risks. However, there are few studies on the adsorption of DBP by sediment from the TGR, and the adsorption characteristics of surface sediment on DBP are not clear. Therefore, based on the actual sediment contents and particle sizes in the TGR, the kinetics and isothermal adsorption characteristics of surface sediment on DBP were investigated in this study. The results showed that the equilibrium time was 120 min, the adsorption kinetics were more in line with the pseudo-second-order kinetic model, and the sediment in water from the Yangtze River exhibited a higher adsorption rate and maximum adsorption amount on DBP than that observed in deionized water. Additionally, a decrease in DBP adsorption was observed with increasing sediment content, while sediment particle size and specific surface area had a slight influence. Analysis using SEM, TGA and FTIR revealed that organic matter on the sediment surface significantly contributed to DBP adsorption. This study contributes valuable insights into the adsorption characteristics of DBP by the surface sediment from the TGR, providing a scientific foundation for understanding the migration and transformation of DBP in this critical reservoir in China.